2012
DOI: 10.1007/s10792-012-9616-3
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study between clinical grading of anterior chamber flare and flare reading using the Kowa laser flare meter

Abstract: To assess the accuracy of standard clinical grading of aqueous flare in uveitis according to the Standardization of Uveitis Nomenclature consensus, and compare the results with the readings of the laser flare meter, Kowa 500. Two examiners clinically graded the flare in 110 eyes. The flare was then measured using the Kowa laser flare meter. Twenty-nine eyes were graded as anterior chamber flare +2; for 18 of these, the clinicians were in agreement, the rest differed by the order of one grade. The range of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(42 citation statements)
references
References 23 publications
0
39
0
3
Order By: Relevance
“…The slit width was 0-11 mm and was continuously available. 9,10 OCULUS Pentacam (Oculus, Inc.) images were obtained under pupil dilatation with 1% tropicamide. To reduce operator-dependent variables, Pentacam's automatic release mode was used.…”
Section: Flaremeter Kowa Fm-700mentioning
confidence: 99%
See 2 more Smart Citations
“…The slit width was 0-11 mm and was continuously available. 9,10 OCULUS Pentacam (Oculus, Inc.) images were obtained under pupil dilatation with 1% tropicamide. To reduce operator-dependent variables, Pentacam's automatic release mode was used.…”
Section: Flaremeter Kowa Fm-700mentioning
confidence: 99%
“…10,14 Damage to the blood-aqueous barrier immediately after cataract surgery was related to the type of surgery, systemic diseases, incision size, bubble formation, and the mechanical trauma to the uveal tissues. 2,[15][16][17][18] Abell et al 19 demonstrated that lower anterior segment inflammation was observed in FLACS versus manual surgery.…”
Section: Eyementioning
confidence: 99%
See 1 more Smart Citation
“…Historically, aqueous flare is not used as a direct indication of inflammation; this is attributable not only to the fact that a breakdown of the blood-brain barrier may constitute permanent damage, but also that the gradings from clinicians are not universal, consistent, or an accurate depiction of the inflammatory status of a given patient [18]. Most commonly, aqueous flare is graded by direct visualization of the iris on slit lamp biomicroscopy and is highly subjective, based on the clinician's experience [18].…”
Section: Future Directionmentioning
confidence: 99%
“…K. Konstantopoulou et al сравнили результаты биомикроскопии у двух офтальмо-логов [36]. Всего в исследование было включено 110 глаз, и в 35,5 % случаев (39 глаз) выявлены несоответствия показателей степени опалесцен-ции между двумя исполнителями.…”
unclassified